INFLUENCE OF IMMUNOMODULATING AGENTS IMMUNOVAK VP-4 AND PROFETAL ON FUNCTIONAL ACTIVITY OF MONONUCLEAR LEUKOCYTES - E. A. Lebedinskaya; N. K. Akhmatova; O. V. Lebedinskaya; V. A. Chereshnev; S. U. Rodionov; M. V. Kiselevsky (Медицинская иммунология)
Immunomodulating ability of a bacterial preparation (Immunovak VP-4 vaccine), and a compound of eukariotic origin (profetal), the main active component of human α-fetoprotein were under investigation in present study. Culturing of mononuclear leukocytes with the immunomodulatory factors promotes quantitative increase of the cells that express surface antigens specific for cytotoxic lymphocytes, natural killers and natural killer T-cells. Both bio-active preparations possess an expressed anti-cancer effect in vitro, i.e., they induce activation of killing properties of human peripheral blood mononuclear leukocytes, which is accompanied by acquiring their characteristic phenotype.